Analisis Kesulitan Membaca Permulaan Pada Kelas II di SD 3 Padurenan - Sari, Erma Novita; Kusumaningrum, Erliana Vivi; Riswari, Lovika Ardana (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2024)
Focus of this research is on the initial reading difficulties experienced by class II students at SD 3 Padurenan. The main aim of this research is to find out what difficulties are experienced by class II students at SD 3 Padurenan. This research uses a qualitative approach with descriptive analysis methods. The subjects in this research were 5 students class II at SD 3 Padurenan who had difficulty reading at first. Data collection techniques in this research are observation, interviews and documentation. The results of the research showed that students in class II had difficulty distinguishing letters that were almost the same in shape, difficulty reading combinations of consonant letters, and difficulty reading consonant letters ending in vowels. Difficulties that can hinder beginning reading are, not having interest in beginning reading which is still low, students' motivation in beginning reading is also low, there is a lack of parental attention regarding students' beginning reading learning activities, and students having too many play activities so that students' learning to read becomes neglected. So, it can be concluded that class II students at SD 3 Padurenan have difficulty reading at the beginning. The hope of this research can be an evaluation in overcoming students' initial reading difficulties.